PEMANFAATAN WEBSITE SEBAGAI MEDIA PENYEDIA INFORMASI DAN PROMOSI UNIVERSITAS SAHID SURAKARTA - Setiyaji, Raka; Anggitya, Paramastu Titis; ., Musta’an (JURNAL KOMUNITAS, 2017)
Sahid University of Surakarta, 2016. Internet is basically a medium that can help the communication process to be efficient, since the Internet is a medium that can be accessed anywhere anytime. By looking at the benefits of information technology, Sahid Univerisity of Surakarta build an online media application that has been widely used by agencies and educational institutions in providing information and make the application as a media promotions. This research aimed to analyze the usage of website as a media promotion and information provider in Sahid University Surakarta. The methodology used in this research is qualitative descriptive, The main objective of this study is to explain how the university take advantage of the website, as a media provider of information and promotion as well as to provide information to stakeholders Sahid University Surakarta both internally and externally. The Results of this research was the use of the website as a media provider of information and promotion of Sahid University Surakarta. Further expected, USS website can appear more attractive in order to compete with other university websites to maximize the display and optimize the function menu website as a media provider of information and promotion by running a variety of content variants (Adversity Content) are integrated with the online social networking available, eventually a brand can reach a broad community.